Synthesis, Characterization and Biological Studies of Mn(III), Co(II), Ni(II) and Cu(II) Chelates of Polystyrene Schiff Base - Sankar, K.; Nazeera Beevi, A. (Asian Journal of Chemistry, 2011)
The Schiff base of polystyrene with indole-3-acetic acid have been synthesized and complexed with Co(II), Ni(II), Cu(II) and Mn(III). They are characterized by elemental analysis, magnetic susceptibility, IR, UV-visible spectral methods and thermal studies. The electronic spectra along with the magnetic studies suggest octahedral or distorted octahedral geometry for all the chelates. The ligand and its metal complexes were screened for their antimicrobial activity using S. aureus and E. coli microorganisms and found to be moderately active. All these complexes catalyze the decomposition of H2O2, Cu(II) complex being the most active.